Analisis Pelaksanaan Evaluasi Pembelajaran Berbasis Tematik di Madrasah Ibtidaiyah Kabupaten Rejang Lebong - Susilawati Susilawati; Syaripah Syaripah (AR-RIAYAH : Jurnal Pendidikan Dasar, 2019)
This study uses this type of research is qualitative research by conducting field surveys on the implementation of thematic-based learning evaluations. The subject of this study used a purposive sample of all Rejang Lebong Madrasah (MI) Districts consisting of 4 (four) state schools and 8 (eight) schools with private status. It is known that the results of his Thematic RPP are categorized as "Good", then the Thematic RPP Implementation has also been in the "good" category. Forms of assessments and thematic based assessments on K-13 have not met the criteria, only 1 school can show its documentation